The art of theft ebook - Thomas, Sherry (Lady Sherlock, 2019)
Charlotte Holmes, Lady Sherlock, is back solving new cases in the Victorian-set mystery series from the USA Today bestselling author of The Hollow of Fear . As "Sherlock Holmes, consulting detective," Charlotte Holmes has solved murders and found missing individuals. But she has never stolen a priceless artwork—or rather, made away with the secrets hidden behind a much-coveted canvas.   But Mrs. Watson is desperate to help her old friend recover those secrets and Charlotte finds herself involved in a fever-paced scheme to infiltrate a glamorous Yuletide ball where the painting is one handshake away from being sold and the secrets a bare breath from exposure.   Her dear friend Lord Ingram, her sister Livia, Livia's admirer Stephen Marbleton—everyone pitches in to help and everyone has a grand time. But nothing about this adventure is what it seems and disaster is biding time on the grounds of a glittering French chateau, waiting only for Charlotte to make a single mistake...